Kajian Hukum Pencemaran Lingkungan Udara Berkaitan Dengan Usaha Mikro Kecil Dan Menengah Di Kabupaten Cirebon - Silviyah A’delina; Endang Sutrisno; Alip Rahman; Sudarminto Sudarminto (Universitas Serang Raya, 2022)
The existence of human life is very dependent on environmental conditions. Thus the environment has an important role in the survival of the community. However, humans need an effort as an effort to maintain life. The existence of micro, small and medium enterprises (Usaha Mikro, Kecil, dan Menengah/UMKM) is the largest part of the national economy. In Cirebon Regency itself there are still economic activities that cause air pollution. How is the implementation of the policy of the Cirebon Regional Government in an effort to overcome air pollution based on the scale of micro, small and medium enterprises based on Law Number 32 of 2009 and what is the implementation of sanctions by the Regional Government of Cirebon in overcoming air pollution. The purpose of this study is to determine the policies and implementation of sanctions carried out by the Cirebon Regency Government in overcoming air pollution. This research method is a normative juridical research, through a law approach and then described in an analytical descriptive manner. Regional Government of Cirebon carries out an environmental pollution program to tackle air pollution through two major sub-districts, namely first measuring air quality to find sources of pollution, second controlling pollution and environmental damage. The application of sanctions by the Environmental Service to perpetrators of air pollution has not yet resulted in criminal sanctions because they do not yet have an Environmental Supervisory Officer. Sanctions carried out by the Office are administrative sanctions or commonly called reprimands. Regional government of Cirebon requires business owners to have UKL-UPL permits which are used as the basis for environmental permits. The government is also obliged to protect the environment in the regional of Cirebon.